Antimicrobial Activity of SPC13, New Antimicrobial Peptide Purified from Scolopendra polymorpha Venom - C.I., Rodríguez-Alejandro; Gutiérrez, M.C. (Anti-Infective Agents, 2020)
Introduction: Currently animal venoms are considered a potential source of numerous bioactive peptides of biochemical and pharmacological interest, such as peptides with antithrombotic, anticoagulant and antimicrobial activity. Methods: Such is the case of the venom from the genus Scolopendromorpha, where numerous PAMs ranging from 2.5 to 4.4 kDa have been purified, they are broad spectrum isolates only of S. subspinipes mutilans. Results: In this study, an antimicrobial peptide (SPC13) of 13 kDa, present in the venom of Scolopendra polymorpha was purified by electroelution and presented antimicrobial activity against S. aureus and P. aeruginosa with MIC of 45 and 192.5 μg/ml respectively, as well as bacteriostatic activity against E. coli at a concentration of 155μg/ml. Conclusion: Additionally, this peptide has a 20.5% hemolytic activity. A partial sequence of SPC13 showed 98% identity with the histone H3 reported in S. viridis (GenkBank: DQ222181.1).
Keywords: resistance